2019
DOI: 10.2147/ijn.s205736
|View full text |Cite
|
Sign up to set email alerts
|

<p>Silver nanoparticles induce reactive oxygen species-mediated cell cycle delay and synergistic cytotoxicity with 3-bromopyruvate in <em>Candida</em> <em>albicans</em>, but not in <em>Saccharomyces</em> <em>cerevisiae</em></p>

Abstract: Background: Silver nanoparticles (AgNPs) inhibit the proliferation of various fungi; however, their mechanisms of action remain poorly understood. To better understand the inhibitory mechanisms, we focused on the early events elicited by 5 nm AgNPs in pathogenic Candida albicans and non-pathogenic Saccharomyces cerevisiae. Methods: The effect of 5 nm and 100 nm AgNPs on fungus cell proliferation was analyzed by growth kinetics monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 42 publications
4
39
0
1
Order By: Relevance
“…However, the concentration of ions released from PMMA was very low and it was not considered toxic to human cells [28]. The disruption of C. albicans instead occurred even at slight Ag + concentration [51,52,53].…”
Section: Resultsmentioning
confidence: 99%
“…However, the concentration of ions released from PMMA was very low and it was not considered toxic to human cells [28]. The disruption of C. albicans instead occurred even at slight Ag + concentration [51,52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed that Ag NPs exposure could induce mitochondrial damage, glutathione depletion membranes integrity and inflammatory cytokines release [17,18]. Other studies reported that Ag NPs could cause DNA damage, reduce metabolic activity, lower ATP production, arrest cell cycle, and induce chromosomal aberrations, cytotoxic and genotoxic alterations [11,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…ex Andrews) and by por Vitali et al [21] in black poplar (Populus nigra L.). AgNPs have been reported to bind to bacteria producing cell cycle arrest [22], caused by toxicity due to ROS production [23]. In addition, Kim et al [24] demonstrated that AgNPs have an antimicrobial effect bacterial cell membrane surface and modifying the cell potential.…”
Section: Treatments With Antioxidant Agentsmentioning
confidence: 99%
“…In fungi, AgNPs break the cell membrane of hyphae altering the mechanisms of infection [27]. Lee et al [22] report that AgNPs that penetrate the cell increase Ag+ cations, which could affect the electrical potential of the membrane, denaturing proteins, leading to cell cycle arrest. On the other hand, Rónavári et al [28] report growth inhibition of fungi such as Candida, Criptococcus, Microsporum and Trichophyton.…”
Section: Treatments With Antioxidant Agentsmentioning
confidence: 99%